Turkish Validity-Reliability Study of the Celiac Disease-Specific Pediatric Quality of Life Scale - Koçak, Cemal; Sandal, Semih; Çöl, Meltem; Tanca, Aydan Kansu; Kuloğlu, Zarife; Kırsaçlıoğlu, Ceyda Tuna (Turkish Journal of Gastroenterology, 2022)
Background: Celiac disease is an autoimmune enteropathy triggered by the presence of gluten. There are Celiac Disease Dutch-Child Quality of Life Scale, Celiac-Specific Pediatric Quality of Life Scale for children/adolescents patients to measure the quality of life. In this study, due to lack of quality of life scales for children with celiac in Turkey, we aimed at Turkish adaptation of the Celiac-Specific Pediatric Quality of Life Scale. Methods: This methodological study was conducted in Ankara University Faculty of Medicine, Cebeci Hospital Hospital between July 2019 and July 2020. A total of 192 children were included. Reliability was demonstrated by the Cronbach’s alpha coefficient. Structural validity was evaluated using explanatory factor analysis and confirmatory factor analysis. The Statistical Package for Social Sciences (SPSS) 22.0 and Amos were used in analyses. Results: In 8-12 age groups; Cronbach’s alpha was 0.92 in negative emotions dimension, 0.88 in school dimension, and 0.74 in enjoyment dimension. In explanatory factor analysis, Kaiser-Meyer-Olkin measure of sampling adequacy value was 0.698, Bartlett’s test of sphericity was significant (P < .001). Variance explained was 75.8%. In confirmatory factor analysis, X2/df was 3.26, root mean square error of approximation value was 0.07, comparative fit index value was 0.96. In 13-18 age groups; Cronbach’s alpha was 0.87 in social dimension, 0.84 in uncertainty dimension, 0.78 in isolation dimension, and 0.83 in limitations dimension. In explanatory factor analysis, Kaiser-Meyer-Olkin measure of sampling adequacy was 0.684, Bartlett’s test of sphericity was significant (P < .001). Variance explained was 68.6%. In confirmatory factor analysis, X2/sd value was 3.78, root mean square error of approximation value was 0.061, and comparative fit index value was 0.961. Conclusion: Cronbach’s alpha values of the groups were found to be above 0.70. Kaiser-Meyer-Olkin values were above 0.5 in terms of sample size, Bartlett’s tests for sphericity were significant in terms of correlations between variables, root mean square error of approximation values were below 0.08, comparative fit index and goodness of fit index values were above 0.95 in terms of model fit. If the scales have been found to be valid and reliable, it is recommended for use in Turkey. Cite this article as: Koçak C, Sandal S, Çöl M, Kansu Tanca A, Kuloğlu Z, Tuna Kırsaçlıoğlu C. Turkish validity-reliability study of the celiac disease-specific pediatric quality of life scale. Turk J Gastroenterol. 2022;33(3):248-256.